The effect of fluid restriction monitoring guidelines using the Heart Failure Self-Care Application (Aplikasi Perawatan Mandiri Heart Failure/ATRIA) on reducing risk of fluid retention in heart failure patients at Dr. Saiful Anwar Hospital Malang - Ghazyarda Aqilah Setya; Mifetika Lukitasari; Suryanto; Ika Setyo Rini; Hikmawan Wahyu Sulistomo; Cholid Tri Tjahjono Candra; Mohammad Saifur Rohman; Ardian Rizal (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Heart failure patients are often at risk of rehospitalization due to recurrent symptoms such as dyspnea, edema, pulmonary congestion, and rapid weight gain resulting from fluid retention. This study aimed to analyze the impact of guided fluid restriction using the ATRIA application on risk of fluid retention in heart failure patients. The quasi-experimental method was used with a posttestonly control group design. Simple random sampling was carried out to select respondents, with the intervention group given the ATRIA application and the control group receiving a booklet intervention. The study duration was four weeks, with 16 respondents in the intervention group and 15 respondents in the control from Dr. Saiful Anwar Hospital, Malang. Data analysis used an independent sample t-test to assess differences in body and weekly weight changes. The resultsshowed no significant difference in body weight between the intervention and control groups each week (p > 0.05). Similarly, there was no significant difference change in body weight between the two groups (p > 0.05). In conclusion, there is no distinction observed between the ATRIA application and booklet concerning fluid restriction guidelines for reducing risk of fluid retention in heart failure patients. The results suggested that nurses could provide educational services and monitor the condition of heart failure patients using either application or booklet. Future studies are recommended to analyze factors that might impact fluid retention in heart failure patient.